Development of perception of Google+ - Gemrich, Jan; Stříteský, Václav; Motyčka, Luděk; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
The goal of this thesis is to introduce readers with the current state of the market of social networks in the Czech Republic with major focus on evolution of user perception of market rookie -- Google+ -- and with focus on success evaluation of marketing activities led to support this service. All this evaluation is done thanks to a research. The master thesis is split into 3 units, which gradually describe current perception of social networks, their definition and also the situation on the Czech market. After deeper description of Google+, the research is described. This research is led in order to allow obtaining data that would allow for comparison of situation before and after execution of above mentioned marketing activities executed during summer of 2012. Final unit of this paper focuses on the research data analysis in order to extract the evolution of awareness and of usage of compared social network and of course to offer very detailed look on Google+ itself and to offer the evaluation of efficiency of the marketing activities.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses